(untitled) (Research, Society and Development, 2020)
The risk of dying from COVID-19 increases with age, as most deaths occur in the elderly, especially those with chronic illnesses. Immunosensence increases the vulnerability to infectious diseases and the prognosis for those with chronic diseases is unfavorable. Thus, this study aimed to describe the relationship between heart failure and COVID-19 infection with an emphasis on the elderly. Descriptive and analytical study of Integrative Literature Review. To carry out this study, the following databases were consulted: Medical Literature Analysis and Retrieval System Online (MEDLINE), Scholar Google, Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO). The Health Sciences Descriptors (DeCS) were used in an associated way: “Heart failure”, “heart”, “Covid-19”, “Coronavirus” and “Elderly”. After applying the inclusion criteria, 9 studies remained. Heart failure patients often experience shortness of breath under stress and these patients may also have a common cold or seasonal flu, and have greater difficulty in breathing. However, if the patient’s symptoms are rapidly progressive and breathing becomes difficult with minimal activity and is accompanied by fever and dry cough, it is necessary to contact a doctor or nurse.